2004
DOI: 10.1128/jb.186.24.8363-8369.2004
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Bypass of Chaperone by Extended Coiled-Coil Motif in T4 Tail Fiber

Abstract: The distal-half tail fiber of bacteriophage T4 is made of three gene products: trimeric gp36 and gp37 and monomeric gp35. Chaperone P38 is normally required for folding gp37 peptides into a P37 trimer; however, a temperature-sensitive mutation in T4 (ts3813) that suppresses this requirement at 30°C but not at 42°C was found in gene 37 (R. J. Bishop and W. B. Wood, Virology 72:244-254, 1976). Sequencing of the temperaturesensitive mutant revealed a 21-bp duplication of wild-type gene 37 inserted into its C-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…To test this possibility, Goldberg and colleagues (including one of this review's authors, PH) constructed phage containing even longer duplications of the putative coiled-coil α-helix (Qu et al 2004). These motifs consist of a minimal amino acid heptad which forms two turns of an α-helix.…”
Section: The Gp37 Tip and Collar Domainsmentioning
confidence: 99%
“…To test this possibility, Goldberg and colleagues (including one of this review's authors, PH) constructed phage containing even longer duplications of the putative coiled-coil α-helix (Qu et al 2004). These motifs consist of a minimal amino acid heptad which forms two turns of an α-helix.…”
Section: The Gp37 Tip and Collar Domainsmentioning
confidence: 99%
“…Sequencing revealed that the mutant gp37 had a duplication of a sequence in its C terminus . Recognizing that the duplicated sequence included hydrophobic heptad repeats, Qu et al introduced artificial coiled‐coil‐forming sequences into wild‐type gp37 and found that this was sufficient to bypass the need for the P38 chaperone . Moreover, multiple coiled‐coil‐forming insertions allowed phage function at extremely high temperatures .…”
Section: Folding Chaperones Modify the Characteristics Of Ts Mutantsmentioning
confidence: 99%
“…Recognizing that the duplicated sequence included hydrophobic heptad repeats, Qu et al introduced artificial coiled‐coil‐forming sequences into wild‐type gp37 and found that this was sufficient to bypass the need for the P38 chaperone . Moreover, multiple coiled‐coil‐forming insertions allowed phage function at extremely high temperatures . By promoting early homomeric gp37 associations even at temperatures that destabilized wild‐type gp37 assembly/folding intermediates, the extra‐coiled coils were sufficient to direct the proper assembly of the tail fiber without assistance from P38.…”
Section: Folding Chaperones Modify the Characteristics Of Ts Mutantsmentioning
confidence: 99%
“…However, the mechanisms involved in these phages' abilities to infect different hosts have not been elucidated. To determine the sequence which might be involved in Kpp95 adsorption, we tried to obtain Kpp95 gene 37 by PCR amplification with primers specific to T4 gene 37 (37RV-1F [5Ј-GTTCTGGTAATTTTGCTAAC-3Ј] and 37RV-1R [5Ј-A ACAGCTAACTTTGGATATG-3Ј], FR86 [5Ј-GCTTCAAGT ACTGACTTAGG-3Ј], and FR89 [5Ј-ACAGTGATAGTATG ACCATGTGATCC-3Ј]) (37,49). However, the reactions failed to give a PCR product.…”
Section: At Least 26 Virion Proteins Of Kpp95 Can Be Visualized By Sdmentioning
confidence: 99%